Photosystem‐II shutdown evolved with Nitrogen fixation in the unicellular diazotroph Crocosphaera watsonii. (21st January 2016) - Rabouille, Sophie; Claquin, Pascal
Summary: Protection of nitrogenase from oxygen in unicellular Cyanobacteria is obtained by temporal separation of photosynthesis and diazotrophy through transcriptional and translational regulations of nitrogenase. But diazotrophs can face environmental situations in which N2 fixation occurs significantly in the light, and we believe that another control operates to make it possible. The night‐time shutdown of PSII activity is a peculiar behaviour that discriminates C rocosphaera watsonii WH8501 from any other phototroph, whether prokaryote or eukaryote. This phenomenon is not only due to the plastoquinone pool redox status, and suggests that the sentinel D1 protein, expressed in periods of nitrogen fixation, is inactive. Results demonstrate a tight constraint of oxygen evolution in C . watsonii as additional protection of nitrogenase activity and suggest a possible recycling of cellular components.